Pengaruh Kerjasama Tim, Motivasi Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada UD. Dian Coklat Papar Kabupaten Kediri - Shinta Mifta Mulida; Ahmad Jauhari; Nur Hidayati (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Human Resource Management (HR) is an important asset in government and private companies. Human resources will organize and manage other resources owned by the company to realize the company's vision and mission. By taking a sample of 35, namely all UD. Dian Coklat Papar uses correlation and regression analysis techniques. The results of the analysis concluded: 1) Teamwork has a positive and significant effect on the performance of UD. Dian Brown Papar. 2) Work Motivation has a negative and significant effect on the performance of UD. Dian Brown Papar. 3) Work Discipline has a positive and significant effect on the performance of UD. Dian Brown Papar. 4) Simultaneously, it is known that there is a significant influence between teamwork, work motivation and work discipline on the performance of UD. Dian Brown Papar.